Hydrogeologic Framework of the New Jersey Coastal Plain: Regional Aquifer-System Analysis - Zapecza, Otto S. : US Department of the Interior : US Geological Survey (US Department of the Interior : US Geological Survey, 1984)
This report presents the results of a water-resources-oriented subsurface mapping program within the Coastal Plain of New Jersey. The occurrence and configuration of 15 regional hydrogeologic units have been defined, based primarily on the interpretation of borehole geophysical data. The nine aquifers and six confining beds are composed of unconsolidated clay, silt, sand and gravel, and range in age from Cretaceous to Quaternary. Open-File Report 84-730 Purpose: To present the results of a water-resources-oriented subsurface mapping program within the Coastal Plain of New Jersey.